PENGARUH UMUR PERUSAHAAN, UKURAN PERUSAHAAN, LEVERAGE, LIKUIDITAS, PROFITABILITAS DAN KINERJA LINGKUNGAN HIDUP TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) TAHUN 2012 – 2015 - Nur Aini; Yeye Susilowati; Kentris Indarti; Ratna Fauziyyah Age (Faculty of Economic and Business Universitas STIKUBANK, 2017)
This study aims to examine and analyze the Influence of Corporate Age, Company Size, Leverage, Liquidity, Profitability and Environmental Performance on Disclosure of Islamic Social Reporting on companies listed in Jakarta Islamic Index (JII) in 2012 – 2015. Object of research on companies listed in Jakarta Islamic Index (JII) in the first period in 2012 - 2015 and obtained 56 companies that become the sample. Sampling technique using purposive sampling. The data analysis used in this research is OLS (Ordinary Least Squerst) multiple linear regression, to get a complete picture about the influence of each independent variable to the dependent variable.The results of this study found firm age, firm size, and liquidity significantly positive impact on the disclosure of Islamic social reporting, while leverage, Profitability and Environmental performance does not affect the disclosure of Islamic social reporting. Keywords: ISR, age of firm, company size, leverage, liquidity, profitability, environmental performan